Mediterranean Diet Index (KIDMED) adherence, socioeconomic determinants, and nutritional status of Portuguese children: the Eat Mediterranean Program - Rito, Ana (2019)
Background: Despite its health benefits, adherence to the Mediterranean diet (MD) has been decreasing, particularly in young generations and in Mediterranean regions, including Portugal. Socioeconomic and lifestyle factors have been shown to influence children and adolescents’ eating habits. This study aimed to assess the association between socioeconomic factors and children’s nutritional status with the MD adherence using the Eat Mediterranean (EM) program. Methods: Participant’s BMI and adherence to the MD diet was assessed at baseline and after the intervention. Data regarding socioeconomic status and KIDMED Index were collected using a family record form. The intervention consisted of various educational sessions addressing the principles and promoting a Mediterranean dietary pattern in schools belonging to two municipalities in the central area of Portugal. A total of 1,772 participants (from preschool to secondary school) met the inclusion criteria for the study. Results: At the end of the program, the adherence to the MD diet improved significantly with participants increasing their adherence to an optimal diet by 17.6%. Daily intake of foods belonging to the MD diet also increased significantly, and the intake of high energy density foods decreased. Mother’s educational level and household income were significantly (p < 0.0001) associated with optimal MD adherence by participants, in both stages. Nutritional status was not associated with the KIDMED Index. Discussion: The EM program showed to be effective in increasing MD adherence in this study population since optimal MD adherence was reported in most participants at the end of the EM program. Household income and mother’s educational level were positively associated with the diet quality of the children and adolescents.